PERAN MANAJEMEN LABA DALAM MEMEDIASI HUBUNGAN ANTARA MEKANISME GOOD CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY, DAN KINERJA KEUANGAN PERUSAHAAN (Studi Empiris pada Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indonesia pada Tahun 2018-2019) - Ferrel Aristo Putro; Imam Ghozali (Diponegoro Journal of Accounting, 2021)
ABSTRACTThis study examines the role of earnings management in mediating the relationship between good corporate governance (GCG) mechanism, corporate social responsibility (CSR), and corporate financial performance. This study's independent variables are good corporate governance (GCG) mechanism and corporate social responsibility (CSR). The mediating variable in this study is earnings management. Meanwhile, the dependent variable in this study is the company's financial performance. This study uses secondary data from annual reports and financial information of non-financial companies listed on the Indonesia Stock Exchange and the Bloomberg database. The sampling method in this study uses a purposive sampling method. It consists of 92 non-financial companies that published their annual reports and were listed on the Indonesia Stock Exchange in 2018-2019. The analytical method used in this study is the partial least square method. The results showed that good corporate governance has a negative impact on corporate financial performance. Corporate social responsibility has a positive impact on corporate financial performance. Good corporate governance has a positive impact on earnings management. Corporate social responsibility has a positive impact on management earnings. Furthermore, this study found no significant impact on the relationship between earnings management on corporate financial performance.